Regulation of Banking Policies That Brings Implication for Criminal Act - Surti Yustianti; Daniel Susilo; Mohammad Roesli (Faculty of Law, Merdeka University Surabaya, 2019)
This research analyzes banking policy regulations that have implications for criminal acts. Decisions made by Bank Indonesia are in accordance with the authority and position pinned to Bank Indonesia officials. Policies made by Bank Indonesia can be appropriate or inappropriate with the principle of prudence and good faith. Bank Indonesia officials have authority related to their position. Bad ethics and inadvertent in making policies can cause state financial losses. As a result, the policy can be categorized as a criminal offense in banking sector. This is normative legal research. This study uses a legislative, conceptual, case and comparative approaches. Banking policies that have an impact on criminal acts can be seen from administrative, civil and criminal aspects related to the mistakes made by Bank Indonesia officials. If a Bank Indonesia official commits an error in implementing policy rules, criminal responsibility must be borne by the official.